GESTÃO DE PROCESSOS DE AFASTAMENTO PARA PÓS-GRADUAÇÃO STRICTO SENSU DOS SERVIDORES DA UNIVERSIDADE FEDERAL DO MARANHÃO (UFMA): uma solução tecnológica para a Pró-Reitoria de Gestão de Pessoas (PROGEP) - SOUSA, Caissa Juliana Silva (2022)
In a scenario marked by the use of technology to solve problems in routine’s work of institutions, the search for process automation provides significant benefits, such as increased productivity, generation of resource savings and reduction of errors. In Federal University of Maranhão (UFMA), the removal processes for stricto sensu postgraduate studies are subject to legal regulations that require the submission of documents within certain deadlines. In this way, this work proposes to develop an information system aiming to present a technological solution to assist the Dean of Personnel Management (PROGEP) in managing the removal processes for stricto sensu graduate programs of UFMA servers, leading to the compliance with rules and deadlines with greater reliability. In methodological terms, it is an applied research, in which the result is a technological product (software development) with practical application. In order to reach the main objective, the design of the software and its functionalities was carried out and, preliminarily, a prospective study was carried out to identify the existence of systems registered at the National Institute of Industrial Property (INPI) with the same purpose as planned. in the present work. Based on the prospective study carried out, it is concluded that, until March 2022, no computer program registered with the INPI was found that aims to manage removal processes for postgraduate studies in higher education institutions. Subsequently, the implementation of the software, the preparation of the instruction manual and the design of a brand for the management of the program began. The initial version of the software was completed and after testing and validation, the registration was submitted for analysis by the INPI. Based on the finalized software, the instruction manual for users was defined. The design of the brand, yet another technological product, was concluded and is undergoing a merit examination at the INPI.